1985
DOI: 10.1002/pol.1985.170230804
|View full text |Cite
|
Sign up to set email alerts
|

Binding of metal ions by polyethylenimine and its derivatives

Abstract: Measurements have been made of the binding of divalent metal ions, Cu2+, Ni2+, Co2+, and Zn2+ ions, by polyethylenimine (PEI) and its acetyl or alkyl derivatives by the equilibriumdialysis technique. These metal ions, in particular the Cu2+ ion, exhibited tremendously remarkable binding affinity toward PEI. The extent of complexation of the polymer with the metal ions was decreased markedly by acetylation or alkylation of the polymer. PEI with no primary amine showed an appreciable decrease in its affinity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…2) became bimodal, and this suggested that growth was by the agglomeration of particles rather than by a simple expansion of individual nanoparticles. This was consistent with the known affinity of primary amines (which account for about 25% of the amines in PEI for divalent cations) 32…”
Section: Resultssupporting
confidence: 88%
“…2) became bimodal, and this suggested that growth was by the agglomeration of particles rather than by a simple expansion of individual nanoparticles. This was consistent with the known affinity of primary amines (which account for about 25% of the amines in PEI for divalent cations) 32…”
Section: Resultssupporting
confidence: 88%
“…The ratio -NH 2 :-NH-:-N= can be measured experimentally by 13 C-NMR (see Figure 3a), and varies typically between 39:37:24 and 32:30:39 for most of the samples analyzed from different suppliers. 43 These functional groups can bind directly to a large number of ions in water solution, 61,62 , and for optimum results -NH-:-N= should be kept between ≈1.1-1.5. On the other hand, although water solutions of PEI present a very high pH, -NH 2 and -NH-protonate below pH≈10 and pH≈6, respectively (see Figure 3b).…”
Section: Preparation Of Stable Solutions For Polymer Assisted Deposition Of Thin-filmsmentioning
confidence: 99%
“…This ligand role property results in some advantages of the composite material such as water solubility, high capacity for metal uptake, easy separation of polymer complexes, high flexibility of the molecular conformation, and good chemical and physical stability [69][70][71].…”
Section: Microgel As Aunp Immobilizermentioning
confidence: 99%